2008
DOI: 10.1073/pnas.0806465105
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-bound mitogen-activated protein kinases transmit dynamic signals in transcription complexes in β-cells

Abstract: MAPK pathways regulate transcription through phosphorylation of transcription factors and other DNA-binding proteins. In pancreatic ␤-cells, ERK1/2 are required for transcription of the insulin gene and several other genes in response to glucose. We show that binding of glucose-sensitive transcription activators and repressors to the insulin gene promoter depends on ERK1/2 activity. We also find that glucose and NGF stimulate the binding of ERK1/2 to the insulin gene and other promoters. An ERK1/2 cascade modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 47 publications
4
71
0
Order By: Relevance
“…Activation of these kinases by IL-1␤ resulted in their rapid association with the insulin gene promoter in human islets as assessed by chromatin immunoprecipitation (ChIP) (Fig. 2 B-D), as was previously shown for glucose-induced activation of ERK1/2, its effector kinase Rsk, and calcineurin (22). Sequential ChIP suggested that the three MAPKs and the ERK effector kinase Rsk were bound to the same DNA fragments (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Activation of these kinases by IL-1␤ resulted in their rapid association with the insulin gene promoter in human islets as assessed by chromatin immunoprecipitation (ChIP) (Fig. 2 B-D), as was previously shown for glucose-induced activation of ERK1/2, its effector kinase Rsk, and calcineurin (22). Sequential ChIP suggested that the three MAPKs and the ERK effector kinase Rsk were bound to the same DNA fragments (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Inhibition is paralleled by loss of several factors that stimulate and a gain of factors own to inhibit insulin gene transcription (20,22) (Fig. 5, models).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the fact that both ERK1/2 and PKB inhibition seem to reverse the effects of ISO stimulation on these identified genes would seem to indicate that both pathways play a role in the regulation of gene expression by nuclear βARs. This may be through MAPK or PKB modulation of the signalling proteins themselves, modulation of the transcriptional machinery or via alterations in the occupancy of chromatin sites by ERK and other protein kinases [43,44]. Further, given the already identified role of MAPKs in regulating mRNA stability [45], further experiments need to be conducted to determine if the regulation that we see is actually due to a changes in the level of de novo mRNA synthesis or reduced mRNA stability.…”
Section: Discussionmentioning
confidence: 94%